When to Consider a Diagnosis of Maturity-Onset Diabetes of the Young: Precise Diagnosis Leads to Better Management and Quality of Life for the Patients - Yujia Gao; Kalyan Mansukhbhai Shekhda; Sarah N. Ali (Avicenna Journal of Medicine)
Maturity-onset diabetes of the young (MODY) is often misclassified and can significantly impact the management of these patients and their families. We present three cases initially diagnosed as type 1 diabetes mellitus (T1DM), type 2 diabetes mellitus (T2DM), and fasting hyperglycemia, which were later identified as MODY. A 38-year-old Caucasian lady, previously diagnosed with T2DM, was referred to the diabetes antenatal clinic. She was treated with gliclazide and metformin before pregnancy. She required insulin glargine during her pregnancy. Her diabetes autoantibodies were negative. MODY was suspected and genetic testing confirmed HNF1A MODY gene mutation. A 57-year-old Caucasian lady was diagnosed with T1DM at the age of 18 years. Since diagnosis, she was treated with insulin glargine without any short-acting insulin, yet persistently suffered from hypoglycemia. MODY was suspected and genetic testing confirmed HNF4A gene mutation. A 33-year-old South Asian lady was referred to a diabetes clinic for suspected T2DM due to strong family history of T2DM, ethnicity, and persistently elevated fasting blood glucose levels. Her genetic testing confirmed GCK-MODY (Glucokinae-maturity-onset diabetes of the young). MODY represents a group of genetic diabetes that can often go unrecognized due to misdiagnosis. Achieving an accurate diagnosis is important as it guides appropriate treatment strategies, improves patient outcomes, and has an impact on other family members due to the hereditary nature of the condition. Employing a systematic approach is crucial. Our cases highlight that it is never too late to challenge the diabetes classification.